2011
DOI: 10.1152/ajprenal.00418.2010
|View full text |Cite
|
Sign up to set email alerts
|

A PPARγ agonist inhibits aldosterone-induced mesangial cell proliferation by blocking ROS-dependent EGFR intracellular signaling

Abstract: Mesangial cell (MC) proliferation is a key feature in the pathogenesis of a number of renal diseases. Peroxisome proliferator-activated receptor-␥ (PPAR␥) has attracted considerable attention for its effects on stimulating cell differentiation and on inducing cell cycle arrest. We previously showed that aldosterone (Aldo) stimulates MC proliferation via the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway, which was dependent on reactive oxygen species (ROS)-mediated epithelial growth factor receptor (EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…For example, they were able to reduce proteinuria and fibrotic responses and prevent podocyte as well as vascular injury, in both animal and clinical trials (87,121). Rosiglitazone, one of the TZDs, can effectively inhibit podocyte injury and MC proliferation through reduced ROS production and recovery of mitochondrial electron transport function in vivo and in vitro (65,154,160). TZDs also decrease TGF-␤ production in glomeruli, thus attenuating renal interstitial fibrosis (74).…”
Section: Treatment Of Mitochondrial Dysfunction-induced Kidney Injurymentioning
confidence: 99%
“…For example, they were able to reduce proteinuria and fibrotic responses and prevent podocyte as well as vascular injury, in both animal and clinical trials (87,121). Rosiglitazone, one of the TZDs, can effectively inhibit podocyte injury and MC proliferation through reduced ROS production and recovery of mitochondrial electron transport function in vivo and in vitro (65,154,160). TZDs also decrease TGF-␤ production in glomeruli, thus attenuating renal interstitial fibrosis (74).…”
Section: Treatment Of Mitochondrial Dysfunction-induced Kidney Injurymentioning
confidence: 99%
“…Several studies have revealed that the renal mesangial cell (MC) is a target local of aldosterone (Aldo) action, where Aldo can induce glomerular injury characterized by mesangial matrix expansion and cell overgrowth through mineralcorticoid receptor (MR) activation [6][7][8], ROS generation, epithelial growth factor receptor (EGFR) phosphorylation, cell cycle-regulatory protein expression, and multiple signaling pathways [8][9][10]. However, the actual molecular mechanism responsible for Aldo-induced MC proliferation is far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the presence of connexins within the kidney and their functional role in growth regulation [8,[11][12][13], analysis of connexins provides a new viewpoint for investigating CKD. Connexins are a multi-gene family of transmembrane proteins with ~20 isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…A key finding is that PPARγ agonists, including troglitazone, rosiglitazone, and prostaglandin J2, significantly decrease the increased expression of TNFα and IL-6 (19). Rosiglitazone inhibits mesangial cell proliferation by blocking reactive oxygen species (ROS)-dependent epidermal growth factor receptor (EGFR) intracellular signaling, and telmisartan has powerful anti-infl ammatory action via PPARγ activation in mesangial cells (20). PPARγ may prove to be a pharmacological target for treatment of glomerulonephritis (19).…”
Section: Discussionmentioning
confidence: 99%